EFFECT OF MACA (Lepedium Meyenii) POWDER SUPPLEMENT ON GROWTH PERFORMANCE AND NUTRIENT DIGESTIBILITY OF YANKASA RAMS (FUDMA JOURNAL OF SCIENCES, 2023)
The use of phytochemical feed additives such as Maca (Lepedium meyenii) has been widely used by livestock farmers to reduce cost of production, toxic and residual effect of industrially chemical synthetic antibiotics and growth promoters. Therefore, this research was conducted to evaluate the effect of Maca power supplement on growth performance and nutrient digestibility of Yankasa rams. A total of twenty (20) grower Yankasa rams was divided into four treatment groups of 0, 5, 10, 15g/ Kg powdered Maca with five (5) rams each per treatment in a completely randomized design (CRD). The growth performance result revealed that all parameters were significantly (P0.05) of initial weight were T4 had the best growth performance attributes followed by T3. Profound (P
Keywords: Maca; Growth; Digestibility; Yankasa Rams